Population Pharmacokinetic Characteristics of Amikacin in Suspected Cases of Neonatal Sepsis in a Low-Resource African Setting: A Prospective Nonrandomized Single-Site Study - Seth K. Amponsah, PhD; George O. Adjei, MD, PhD; Christabel Enweronu-Laryea, MRCPCH; Kwasi A. Bugyei, PhD; Kosta Hadji-Popovski, MSc Pharm; Jorgen A.L. Kurtzhals, MD, PhD; Kim Kristensen, PhD (Elsevier, 2017)
Background: Amikacin exhibits marked pharmacokinetic (PK) variability and is commonly used in combination with other drugs in the treatment of neonatal sepsis. There is a paucity of amikacin PK information in neonates from low-resource settings. Objectives: To determine the PK parameters of amikacin, and explore the influence of selected covariates, including coadministration with aminophylline, on amikacin disposition in neonates of African origin. Methods: Neonates with suspected sepsis admitted to an intensive care unit in Accra, Ghana, and treated with amikacin (15 mg/kg loading followed by 7.5 mg/kg every 12 hours), were recruited. Serum amikacin concentration was measured at specified times after treatment initiation and analyzed using a population PK modeling approach. Results: A total of 419 serum concentrations were available for 247 neonates. Mean (SD) trough amikacin concentration (from samples collected 30 minutes before the fourth dose) among term (n = 25), and preterm (<37 weeks' gestation n = 36) neonates were 6.2 (3.4) and 9.2 (5.7) µg/mL, respectively (P = 0.02). A 1-compartment model best fitted amikacin disposition, and birth weight was the most important predictor of amikacin clearance (CL) and distribution (V). The population CL and V of amikacin were related as CL (L/h) = 0.153 (birth weight/2.5)1.31, V (L) = 2.94 (birth weight/2.5)1.18. There was a high between-subject variability (58.9% and 50.7%) in CL and V, respectively. CL and V were 0.058 L/h/kg and 1.15 L/kg, respectively, for a mean birth weight of 2.1 kg, and the mean half-life (based on 1-compartment model), was 13.7 hours. Conclusions: The V and half-life of amikacin in this cohort varied from that reported in non-African populations, and the high trough and low peak amikacin concentrations in both term and preterm neonates suggest strategies to optimize amikacin dosing are required in this population.